MANAGEMENT ANALYSIS OF BARCODE-BASED STUDENT PICKUP DIGITALIZATION SERVICES IN AN EFFORT TO IMPROVE THE QUALITY OF EDUCATION - Husin, Husin; Oktradiksa, Ahwy (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Barcode-based student pick-up digitalization service management is services to improve the quality of education in the form of digitalization implemented at MI Puti Bungsu Al-Muhajirin Denpasar with the aim of provide security and comfort to students' parents. Digitization services This barcode-based student pickup uses three applications, namely Google drive, google forms and google spreadsheets. This research uses qualitative approach. The results of qualitative research seek to understand and interpret the meaning of events interacting with human behavior using descriptive research and using analysis. Research result This shows that the digitalization of student pick-up services is based barcodes as a service to improve the quality of education, especially in the security at MI Puti Bungsu Al-Muhajirin Denpasar. Barcode creation and Implementation is very easy, just use Google Forms and Google spreadsheets. The Google form contains student information and information about being picked up then generate a link from each response, and copy the link that you have obtained in Microsoft Excel, use the formula and generate a link automatically uses the URL so it becomes a barcode. Use The barcode is simply pasted on the monitor screen